(3GdEaUGM Yf eYGfi GdUMGMs - (3jMji Hf (B((3gHjQI Hf(B) (3eMeO Hf gHjQI GdPgdj GdTjHGfqj, CHh GdeXaQ, Yhf GdOjf,J (B560 (3g` s
(3ChdgG (B:s
(3GdMeO ddg cJGH GdWgGQI GLJeYhG Ydi Cf GdUdGI dGJUM GdE HWgGQI EPG hLO GdSHjd EdjgG s
(3BNQgG (B:s
(3hgh bhdg UdiGddg Ydjg hSde ef jQO dGdg Hg NjQ jabgg aiGdOjf hGddg SHMGfg GdeMehO eG hab ef Pdc BNQ GdcJGH s
(3HChdg JedcGJ heWGdYGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B175 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B228s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs